Aplikasi Google Classroom sebagai Media Pembelajaran Online dan Dampaknya Terhadap Keaktifan Belajar Siswa pada Masa Pandemi Covid-19 - Manurung, Roliana; Sadjiarto, Arief; Sitorus, Destri Sambara (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2021)
The objective of the current study was to analyze the google classroom app as an online learning medium and its impact on student learning activity during the covid-19 pandemic. This study applied descriptive method within qualitative approach. The research subjects were students of XI MIPA 1-3 class, economics teacher, and deputy head of the curriculum. The data collection was carried out using observation, interview, documentation and field note, then the results were analyzed using an interactive model from Miles and Hubermen which included data collection, data reduction, data display and drawing conclusion. The results of the study found that the internal factor in the online learning process using google classroom which has an impact on student learning activity is motivation. Meanwhile, student’s interest in learning and readiness to learn does not have an impact on student learning activity. The external factor in the online learning process using google classroom that has an impact on learning activity is parent and teacher support. On the other hand, facilities and infrastructure have no impact on students learning activity. The google classroom app as an online learning media and its impact on student learning activity can be observed from the understanding of learning material, scores, activeness in asking questions and dicipline.